2020
DOI: 10.1101/2020.04.12.20062794
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modelling and analysis of COVID-19 epidemic in India

Abstract: COVID-19 epidemic is declared as the public health emergency of international concern by the World Health Organisation in the second week of March 2020. This disease originated from China in December 2019 has already caused havoc around the world, including India. The first case in India was reported on 30 th January 2020, with the cases crossing 6000 on the day paper was written. Complete lockdown of the nation for 21 days and immediate isolation of infected cases are the proactive steps taken by the authorit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 7 publications
0
37
0
Order By: Relevance
“…Also, the CFR estimates relying on the formula 'death / (recovery + death)' outpace the previous one, because of the consideration of a time delay between diagnosis and death [9,10], and thus explaining that the 14-day delay estimate of CFR is not a real one in exploring COVID-19 case fatality [11,12]. A number of studies including that we have done though demonstrated the estimation of reproduction number [1,2], there is a dearth of reliable CFR estimates of COVID-19 ongoing pandemic particularly of Indian context. In view of the above background this communication explores various estimates of fatalities of COVID-19, along with estimation of doubling time, reproduction number, and serial interval, in estimating COVID-pandemic severity in Indian context.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Also, the CFR estimates relying on the formula 'death / (recovery + death)' outpace the previous one, because of the consideration of a time delay between diagnosis and death [9,10], and thus explaining that the 14-day delay estimate of CFR is not a real one in exploring COVID-19 case fatality [11,12]. A number of studies including that we have done though demonstrated the estimation of reproduction number [1,2], there is a dearth of reliable CFR estimates of COVID-19 ongoing pandemic particularly of Indian context. In view of the above background this communication explores various estimates of fatalities of COVID-19, along with estimation of doubling time, reproduction number, and serial interval, in estimating COVID-pandemic severity in Indian context.…”
Section: Introductionmentioning
confidence: 91%
“…In India, SARS-CoV-2, the causative agent of COVID-19, transmits with a basic reproduction number of 1.03-1.55 [1,2], and as of May 10, 2020, the country registered 2,109 people who succumbed to the disease among 62,939 confirmed cases [3]. Notably, the virus spreads very powerfully from Wuhan of Hubei province in China, the primary epicentre of COVID-19 pandemic, with basic reproduction number 2.2 [4] to the neighboring countries and beyond [5].…”
Section: Introductionmentioning
confidence: 99%
“…Despite all the efforts, the pandemic is still ongoing and researchers are directing increasing efforts towards the comprehension of this disease dynamics by modelling its spread [1], [2], [3], [4], [5], [6], [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…This deterministic model has several alternatives that add components to represent other phenomena in the dynamic. In the case of COVID-19, the work in [1], [2], [3] exploits a variant of the SIR model which introduces also the variable Q to take into account the "quarantined" subpopulation, named SIQR model [9]. In particular the contribution in [1] presents as main case study the modelling of COVID-19 spread in Italy between February 20 and March 10.…”
Section: Introductionmentioning
confidence: 99%
“…The first nation-wide lockdown of 21 days and further lockdowns 2.0, 3.0, and 4.0, was certainly helpful in restricting asymptomatic people. The governmental measures applied so far have substantially reduced the infection rate R 0 (<1.5) with a doubling rate of cases (i.e., cases double every 15 days) for India [MOHFW-GoI 1 ; (43)]. The data available to date suggest a mean death rate of 2.8% for India, which includes 86% comorbidity cases (Figure 2A).…”
mentioning
confidence: 99%